Cytokines and Abnormal Glucose and Lipid Metabolism - Shi, Jie; Fan, Jiangao; Su, Qing; Yang, Zhen (Frontiers in Endocrinology, 2019)
Clear evidence indicates that cytokines, for instance, hepatokine, myokines, adipokines, osteokines and inflammatory cytokines contributing substantially to the development of insulin resistance and type 2 diabetes in autocrine, paracrine and endocrine manners. Some cytokines play a positive role in metabolism action, while others play a negative metabolic role linking to the induction of metabolic dysfunction. The mechanisms involved are not fully understood, but are associated with lipid accumulation in organs and tissues especially in the liver, changes in energy metabolism, and inflammatory signals derived from various cell types, including immune cells. In this review, we describe the roles of certain cytokines in the regulation of metabolism and inter-organ signaling in regard to the pathophysiological aspects in type 2 diabetes. Given the disease-related changes in serum levels of relevant cytokines, these factors may serve as biomarkers for the early detection of type 2 diabetes. Moreover, based on preclinical studies, certain cytokines that can induce improvements in glucose and lipid metabolism and immune response may emerge as novel targets of broader and more efficacious treatments and prevention of type 2 diabetes.